Economic potential of pea farming in Himachal Pradesh - Sharma , Subhash; Barwal, Parul (Indian Farming, 2024)
Pea farming in Himachal Pradesh has a significant economic potential due to the state’s favourable climatic conditions with substantial potential for enhancing farmer incomes and addressing food security. Hilly regions of Himachal Pradesh gain a competitive advantage by growing off-season peas, which allows farmers to capture premium prices in the market. This off-season production boosts profitability for hilly region farmers and adds economic value by meeting demand when supplies from lower hills areas are limited. The article focuses on sowing and harvesting time of pea cultivation, cost of production, and price behaviour of pea across different zones. Moreover, training programmes for farmers on modern farming techniques, climate-smart practices, and business management should be organized to help them increase production and profitability.